2018
DOI: 10.1101/244392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification, expression analysis and molecular modeling of Iron deficiency specific clone 3 (Ids3) like gene in hexaploid wheat

Abstract: 2 6

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…As wheat is a hexaploid with three homeologous genomes there is a high chance that similar genes on the respective homeologous chromosomes would be found. An elaborate study of iron deficiency-specific clone 3 (Ids3)-like genes in hexaploid wheat was conducted by Mathpal et al, 2018. The authors found an ortholog on the telomeric region of chromosome 7A and its homolog ranged from 78% to 88% on chromosomes 7D and 7B.…”
Section: Discussionmentioning
confidence: 99%
“…As wheat is a hexaploid with three homeologous genomes there is a high chance that similar genes on the respective homeologous chromosomes would be found. An elaborate study of iron deficiency-specific clone 3 (Ids3)-like genes in hexaploid wheat was conducted by Mathpal et al, 2018. The authors found an ortholog on the telomeric region of chromosome 7A and its homolog ranged from 78% to 88% on chromosomes 7D and 7B.…”
Section: Discussionmentioning
confidence: 99%
“…Modeled 3D structures from the SWISS-MODEL server were used as the initial configuration of all simulations. The MD simulations were conducted as per the protocol previously described in Gajula et al (2016); Kumar et al (2016Kumar et al ( , 2018aKumar et al ( , and 2018b; Mathpal et al (2018);and Gautam et al (2019). A minimum of 10 Å distance was used between the protein surfaces and the simulation box edges.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…Phylogenetic analysis was performed by using sequences of predicted proteins associated with flag leaf development through Mega-X software (Kumar S. et al, 2018). A phylogenetic tree was constructed using the neighbor-joining method with 1,000 bootstraps for inferring evolutionary relationships.…”
Section: Phylogenetic Analysismentioning
confidence: 99%